Hair follicle specific ACVR1/ALK2 critically affects skin morphogenesis and attenuates wound healing. Issue 3 (21st June 2017) - Sorkin, Michael; Agarwal, Shailesh; Ranganathan, Kavitha; Loder, Shawn; Cholok, David; Fireman, David; Li, John; Li, Shuli; Zhao, Bin; Mishina, Yuji; Cederna, Paul; Levi, Benjamin
Abstract: The bone morphogenic protein signaling (BMP) is intricately involved in the quiescence and regulation of stem cells through activation of BMP receptors. Hair follicle stem cells play a critical role in cutaneous homeostasis and regeneration. Here, we utilize a novel mouse model with targeted overexpression of the BMP receptor ALK2/ACVR1 in hair follicle stem cells, to characterize its role in skin development and postnatal wound healing. Initial histologic evaluation demonstrated significant dysregulation in hair follicle morphogenesis in mutant mice. These demonstrated increased numbers of individual hair follicles with altered morphology and localization. Mutant follicles were found to exhibit elevated proliferative activity as well as increased prevalence of CD34 and ITGA6 positive follicle stem cells. Interestingly, constitutive overexpression of ALK2 resulted in attenuation of cutaneous wound healing. These findings demonstrate that hair follicle specific ALK2 is intricately involved in maintenance of the stem cell niche and wound healing.